The Effect of Trust and Political Participation on Stability in Iraq - Barzan Jawhar Sadeq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The first objective of state formation is to establish stability. Stability establishes security, which builds the way to political, economic and social development. Due to the fact that Iraq is a multi-ethnic, religious, sectarian country, on the other hand, the state is not systematically established, the Iraqi political systems has not been able to obtain long-term stability. For these reasons, there has always been a shaky and weak relationship between the Iraqi people and the political Authority in Iraq. The new Iraq (after 2003) suffers from the same political challenge. This gap between the people and the authorities due to the weakness of the government institutions and the interference of informal officials inside and outside the country, year after year political trust is going down. Public trust in official institutions has weakened, and political participation has declined election after election. So, now political legitimacy in Iraq is under a big question. This research aims to find out the level of trust and political participation in Iraq and the relationship between trust, political participation and stability in Iraq? It tries to find the causes of the decline of trust and political participation and the role of this decline on instability in Iraq? The researcher adopted both quantitative and qualitative methods to collect, analyse and compare theoretical sources, data and figures.